Efisiensi Teknis Penggunaan Input Produksi Pada Usahatani Sawi (Kasus Desa Baumata, Timur Kecamatan Taebenu Kabupaten Kupang, NTT) - Murdolelono, Salsabila L.; Kapa, Maximilian M. J.; Bano, Maria (University of Islam Malang, 2021)
This study aims (1) to analyze the influence of the use of production factors on the amount of mustard production; (2) to analyze the technical efficiency of the use of production inputs in mustard farming in the research area; and (3) to analyze the feasibility of mustard farming in the research area. Determination of the sample of respondent farmers using the method of saturated samples because the members of the population is small (41 people). So the number of respondents was as many as 41 farmers. The results showed that the use of land area input (x1), seeds (x2), organic fertilizers (x3), inorganic fertilizers (x4), pesticides (x5), and labor (X6) simultaneously had a significant effect on mustard production (Î±=0.05), as evidenced by the value of F-stat of 441,015 greater than F table of 2.49. Partially the production factor that has a very significant effect (Î±=0.01) on the increase in mustard production is the land with a regression coefficient of 0.082 and a t-stat value of 8,396, seeds have a real effect (Î±0.05) on mustard production with a regression coefficient value of 0.082 and a t count value of 3,075 and inorganic fertilizers have a noticeable effect (Î±=0.10) on mustard production with a regression coefficient value of 0.065 and a t stat value of 2.125. While other production factors, namely organic fertilizers, pesticides and labor have no real effect on the production of mustard at the research site. The Coefficient of Determination (R2) obtained a value of 0.994 which means that 99,4% of the dependent variable was expamimed by the independent variables while the remaining 0.6% is explained by other variables that are not included in the model. The use of production factors such as land area, seeds, organic fertilizers, inorganic fertilizers and labor in mustard farming was technically efficient, because the value of b > 0. This can be seen from the coefficient of regression of each variable, namely land area (0.395), seeds (0.082), organic fertilizers (0.079), inorganic fertilizers (0.395) and labor (0.002). While the pesticide input production in mustard farming is technically inefficient, because the value of b < 0. This can be seen from the value of pesticide regression coefficient of -0.035. Mustard farming at the research site provides relative profit with the value of R /C Ratio > 1 (R/C= 3.65) so that mustard farming is feasible to be cultivated.